2009
DOI: 10.1111/j.1399-0012.2009.01038.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the coagulation and inflammatory responses in solid organ transplant recipients and donors

Abstract: New strategies that modify the coagulation/inflammatory cascades may be applicable to solid organ transplant (SOT) recipients in the treatment of complications. However, data on kinetics of post‐SOT cascades are needed before considering these strategies. Prospectively collected pre‐transplant serum measurements of inflammatory (high‐sensitive C‐reactive protein, HS‐CRP) and coagulation (d‐Dimer, DD; protein C, PC) markers were compared to post‐operative (day 1–90) values in deceased‐donor liver (DDLT) and ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…Low plasma levels of protein C recipient was associated, in this work, with liver disease relapse (Additional File 2, Table S2), and this fact could be a consequence of disbalance of coagulation factors in terminal cirrhosis [28]. A previous paper had shown that PC was decreased at day 7 (p = 0.04) and day 30 (p = 0.009) in DDLT and DDRT/LRT groups with complications, respectively [29]. Nevertheless, high plasma fibrinogen levels are not a consequence of liver function alteration, and could be an important pro-thrombotic factor in development graft thrombosis that has not been previously described.…”
Section: Discussionmentioning
confidence: 58%
“…Low plasma levels of protein C recipient was associated, in this work, with liver disease relapse (Additional File 2, Table S2), and this fact could be a consequence of disbalance of coagulation factors in terminal cirrhosis [28]. A previous paper had shown that PC was decreased at day 7 (p = 0.04) and day 30 (p = 0.009) in DDLT and DDRT/LRT groups with complications, respectively [29]. Nevertheless, high plasma fibrinogen levels are not a consequence of liver function alteration, and could be an important pro-thrombotic factor in development graft thrombosis that has not been previously described.…”
Section: Discussionmentioning
confidence: 58%
“…Although elevated C-reactive protein is associated with increased cardiovascular events, it has only been studied post-operatively in the ESLD population (31). C-reactive protein appears to peak and slowly fall within 1 week after LT, and delayed elevations may indicate inflammatory complications such as post-operative infection or rejection (32).…”
Section: Coronary Artery Diseasementioning
confidence: 97%
“…The technology employed for biopsy assessment and the resulting diagnostic classification did however not always keep pace with the rapidly evolving knowledge about the mechanisms of rejection [ 2 ]. Therefore, new biomarkers for early predicting renal graft dysfunctions are clearly needed [ 4 , 8 , 9 ]. In this regard, it is well known that the activation of blood coagulation or suppression of fibrinolysis plays a role in the progression of atherosclerosis in renal transplanted patients and it seems to be the major cause of mortality after transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Acute rejection has been associated with activation of inflammatory factors and coagulation cascade during the first three months after renal transplant. Acute rejection may result in graft loss, increased risk of chronic allograft dysfunction, and suboptimal long-term outcome [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation